Renin Gene MboI Dimorphism Is a Discriminator for Hypertension in Hyperlipidaemic Subjects - Kane, John P.; Frossard, Philippe M.; Bener, Abdulbari; Malloy, Mary J. (Hypertension Research, 1999)
As renin is the key enzyme of the renin-angiotensin-aldosterone system, the renin gene (REN) represents a good candidate quantitative trait locus for investigations aimed at uncovering the molecular and genetic influences implicated in the molecular etiology of essential hypertension. Among the various polymorphic markers that are available at the REN gene locus, an MboI dimorphic site located in the ninth intron of the REN gene has previously been shown to be significantly associated with a family history of hypertension in a Japanese population and with direct clinical diagnosis of essential hypertension in a Gulf population. We determined MboI allele and genotype distributions in a sample population of 349 (178 men, 171 women) hyperlipidaemic US Caucasians (mean age 55.4±13.1 yr), comprising 122 hypertensive and 227 normotensive subjects. A statistically significant association was found between alleles on which the MboI site was present [MboI(+)] and clinical diagnosis of hypertension. REN MboI(+) alleles are thus in linkage disequilibrium with genetic influences that contribute to increased individual susceptibility to hypertension of hyperlipidaemic patients (with an associated odds ratio of 2.15, 95% CI: 1.34-3.45). This positive association does not seem to occur through the effect of classical risks factors represented by lipid, lipoprotein and apolipoprotein levels. (Hypertens Res 1999; 22: 285-289)